2014
DOI: 10.1007/s10549-014-3185-2
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of tumor-infiltrating lymphocytes in triple-negative breast cancer: a meta-analysis

Abstract: In a recent meta-analysis, we demonstrated that rich tumor-infiltrating lymphocytes (TILs) were significantly correlated to a favorable breast cancer (BC) outcome largely in estrogen receptor-negative tumors. It is known that TILs predominate in triple-negative (TN) BC, and to the best of our knowledge, there is no published meta-analysis that examined their prognostic value exclusively in that subtype. Therefore, we planned this meta-analysis to explore the clinical utility of rich TILs in TN-BC. According to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
172
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(192 citation statements)
references
References 32 publications
16
172
1
3
Order By: Relevance
“…As previously reported in other meta-analyses of randomized and nonrandomized trials, our results suggest that TNBC patients with a particularly strong lymphocytic infiltrate (i.e., LPBC) were more likely to experience pCR compared with patients with low lymphocytic infiltrate [19,24]. In the adjuvant setting, despite the good prognosis of TNBC patients with very high sTILs, these patients should not be spared chemotherapy in light of the recentdata derived from two RCTs comparing adjuvant anthracyclines (which induce immunogenic cell death in preclinical models) versus no adjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 88%
“…As previously reported in other meta-analyses of randomized and nonrandomized trials, our results suggest that TNBC patients with a particularly strong lymphocytic infiltrate (i.e., LPBC) were more likely to experience pCR compared with patients with low lymphocytic infiltrate [19,24]. In the adjuvant setting, despite the good prognosis of TNBC patients with very high sTILs, these patients should not be spared chemotherapy in light of the recentdata derived from two RCTs comparing adjuvant anthracyclines (which induce immunogenic cell death in preclinical models) versus no adjuvant chemotherapy.…”
Section: Discussionsupporting
confidence: 88%
“…The value of evaluating tumor-infiltrating leucocytes (TIL) as a diagnostic, prognostic, and predictive biomarker in breast cancer has now been shown by a range of studies (1)(2)(3)(4)(5). In many of these studies, the evaluation of TIL was based on H&E-stained sections and recommendations around the conduct of this effective and simple "immunoscore" may improve the standardization for clinical implementation (6).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance to these studies, a meta-analysis including 16,097 patients found that rich in TILs ER− breast carcinomas were associated with favorable prognosis (33). High TILs were associated with response to neoadjuvant chemotherapy (38), in two meta-analyses including 3,251 patients (39) and 12,968 patients (40), in ER− breast carcinomas, according to a meta-analysis with 16,097 patients (33), in HER2+ breast carcinomas and TNBC (41).…”
Section: Hande Markers Prognostic/predictive For Disease Outcomementioning
confidence: 72%
“…A meta-analysis of TILs in early, TNBCs noted that TIL-rich TNBCs were associated with better OS (HR 0.66, 95% CI: 0.53-0.83) irrespectively of TIL location (intratumoral or stromal) or mode of detection (H&E, CD8+ or Foxp3+ populations) (33).…”
Section: Prognostic Individual Ihc Markers For Disease Outcomementioning
confidence: 99%